Lipoproteins Role in Health and Diseases - Frank, Sasa; Kostner, Gerhard (IntechOpen, 2012)
By typing into databases such as Medline or PubMed the word "lipoprotein" one gets more than 100.000 hits that highlight the common interest in this topic. It is actually impossible to cover all aspects of lipoprotein structure, function, metabolism and pathophysiology in one issue like the present volume, but attempts have been made to concentrate on topics that are in focus of current lipoprotein research. These topics have been divided into 10 sections. This volume will help new investigators in the field to get acquainted with the general topic of lipoprotein research and will guide scientists interested in this area to emerging new fields.